Imagens de satélite na análise da relação entre queimadas, aerossóis atmosféricos e precipitação - Prado, Nathália Velloso [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The direct and indirect effects of atmospheric aerossols in the amazonic climate have been focus of many published. This work aims to analyze a possible relation among Burns, atmospheric aerossols and precipitation above South America. It uses the avaluable data from the satellites AQUA/TERRA and TRMM and the images furnished by NOAA and GOES. These analysis can provide some explanations about the effects of emission of aerosols by burns on the composition of atmosphere and cloud formation, mainly in Amazon. We use the Aerosol Optical Depth (AOD) from MODIS/TERRA-AQUA, burns index from CPTEC and rain rate from TRMM. The data we use were obtained from 2000 until 2012. The study is divided in two parts. In the first one, it was performed a quantitative analysis between number of burns and aerosols emission. It was identified a great variability in space and time of the AOD on South America. On the north, northeast and center-west, the AOD is significant during the winter period, with peak on August and September. The southeast is affected by aerosols from center-west due to the dynamical transport. In the second part, it was evaluated the relation between AOD and precipitation in a 13-year period. The statistical analysis shows up a negative correlation of 0.72 between August and October, on Legal Amazon. These result indicate an inverse relation between AOD and rain rate. The other months present not significant correlation. These results are in a good agreement with the literature, in which in-situ methods were applied or combined with satellites data. The increasing of aerosols concentration in the atmosphere are reinforced during drier years. It can affect the increasing process of water drops, decreasing the precipitation. We also verified higher values of AOD (0.25 - 0.3) during years with El Niño, than the climatologically average (~0.15 - 0.2), ... (Complete abstract click electronic access below)

Os efeitos diretos e indiretos dos aerossóis atmosféricos no clima amazônico têm sido tema de várias pesquisas. O objetivo deste estudo foi analisar a possível relação entre as queimadas, aerossóis atmosféricos e a precipitação sobre a América do Sul, explorando a disponibilidade de dados dos satélites AQUA/TERRA, TRMM e as imagens produzidas no CPTEC/INPE que utilizam produtos dos satélites NOAA e GOES. Esta análise poderá gerar conhecimento sobre os efeitos da emissão de aerossóis pelas queimadas na composição da atmosfera e no processo de formação de nuvens, principalmente na Amazônia. Para isso, foram analisados os dados de satélite do período de 2000 a 2012, referentes à profundidade óptica de aerossol (MODIS/TERRA-AQUA), detecção de queimadas (produzidos no CPTEC) e à taxa de chuva (TRMM). O estudo foi elaborado em duas etapas distintas. Na primeira etapa foi realizada a análise qualitativa entre o número de queimadas e a emissão de aerossóis, sendo identificada uma grande variabilidade espacial e temporal da profundidade óptica de aerossol (AOD = Aerossol Optical Depth) sobre a América do Sul. As regiões norte, nordeste e centro-oeste apresentam AOD marcante nos meses de inverno, com pico no mês de agosto e início de setembro. A região sudeste é afetada pela emissão de aerossol da região centro-oeste em decorrência do transporte dinâmico. Na segunda etapa foi avaliada a relação entre AOD e precipitação, por meio da análise de correlação no período de 13 anos. As análises estatísticas, realizadas sobre grande parte da área da Amazônia Legal, mostraram uma correlação negativa de 0,72 entre os meses de agosto a outubro. A correlação negativa indicou que altos valores de AOD apresentam uma relação com baixos valores de taxa de precipitação. Os demais meses apresentaram baixa ... (Resumo completo, clicar acesso eletrõnico abaixo)
Keywords: Sensoriamento remoto; Ar - Qualidade; Aerossois; Queimada; Remote sensing